2008
DOI: 10.1093/carcin/bgn124
|View full text |Cite
|
Sign up to set email alerts
|

Alkenyl group is responsible for the disruption of microtubule network formation in human colon cancer cell line HT-29 cells

Abstract: Alk(en)yl trisulfides (R-SSS-R′) are organosulfur compounds produced by crushed garlic and other Allium vegetables. We found that these compounds exhibit potent anticancer effects through the reaction with microtubules, causing cell cycle arrest. Nine alk(en)yl trisulfides including dimethyl trisulfide, diethyl trisulfide, dipropyl trisulfide (DPTS), dibutyl trisulfide, dipentyl trisulfide, diallyl trisulfide (DATS), dibutenyl trisulfide, dipentenyl trisulfide and allyl methyl trisulfide were synthesized and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…28) However, our present study is the first to show that SH-compounds cancel the antibiotic properties of garlicderived allicin and authentic allicin, and to discuss the molecular interaction of allicin with intra-and intercellular components.…”
Section: )mentioning
confidence: 64%
“…28) However, our present study is the first to show that SH-compounds cancel the antibiotic properties of garlicderived allicin and authentic allicin, and to discuss the molecular interaction of allicin with intra-and intercellular components.…”
Section: )mentioning
confidence: 64%
“…They have recently demonstrated that DATS-induced microtubule disarrangement and the resulting cell-cycle arrest were completely counteracted by such sulfhydryl reagents as L-cysteine, GSH and NAC, suggesting that exogenous DATS modifies the growth-related proteins at their sulfhydryl groups in the cysteine residues of cellular proteins. 20) The dimethyl trisulfide and tetrasulfide, which also have an -S-S-bond in their structures, may exert a similar effect on the induction of apoptosis to that of DADS and DATS.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] We also reported that DATS induces apoptosis in human colon cell lines by oxidative modification of cysteine residues in β-tubulin into S-allyl cysteine residues; this modification causes cell cycle arrest at M-phase followed by apoptosis. 5,6) On the other hand, we also found that DATS induces apoptosis in human leukemic cells in a cell cycle independent manner; however, the molecular target(s) of DATS remains to be clarified. This study was aimed at clarifying the molecular target of DATS in Jurkat cell by focusing on the oxidative modification of cysteine residue.…”
mentioning
confidence: 81%
“…The ASK1 activates JNK to reduce the mitochondrial membrane potential. 9) Because DATS is highly reactive with cysteine residues, 6) we hypothesized that DATS can form disulfide bond between Cys32 and Cys35 of Trx to activate ASK1. To demonstrate this hypothesis, we examined the effect of DATS on the redox state of Trx by urea-polyacryl amide gel electrophoresis (PAGE) and Western blotting.…”
mentioning
confidence: 99%